2020
DOI: 10.1177/1354816620946541
|View full text |Cite
|
Sign up to set email alerts
|

Biosecurity, crisis management, automation technologies and economic performance of travel, tourism and hospitality companies – A conceptual framework

Abstract: The COVID-19 pandemic of 2020 will have a significant influence on travel, tourism and hospitality (TTH) globally. With a massive reduction in tourism globally because of the health crisis, the industry will have to plan recovery and rebuilding of the industry with greater consideration of the biosecurity of customers. A critical element in the reorganisation of the industry will involve the increased incorporation of automation technologies. This article adopts a supply-side perspective and elaborates on the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 137 publications
(116 reference statements)
3
54
0
Order By: Relevance
“…To reactivate the tourism industry, international organizations are developing new studies to analyze the role that the private sector plays in coping with pandemic COVID-19 [ 40 ]. As a result, managers have the responsibility to develop tools that they can use to prevent or plan for these crises and drivers to guide them during the transition period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reactivate the tourism industry, international organizations are developing new studies to analyze the role that the private sector plays in coping with pandemic COVID-19 [ 40 ]. As a result, managers have the responsibility to develop tools that they can use to prevent or plan for these crises and drivers to guide them during the transition period.…”
Section: Methodsmentioning
confidence: 99%
“…Guidance on the provision of safe water, sanitation, and hygienic conditions has been offered by the WHO since the origin of the spread of the COVID-19 virus [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. According to Luby et al [ 56 ], handwashing reduced the incidence of respiratory infections in children and young adults in previous pandemics.…”
Section: Methodsmentioning
confidence: 99%
“…Robots are widely suggested to be deployed in different scenarios during the pandemic, to help reduce the infection by performing disinfection, monitoring, delivering, food preparation, and telepresence [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ]. Robots are also recommended to make intelligent decisions based on the inputs data from the population, which can be analysed through AI [ 17 ].…”
Section: Robots In Covid-19mentioning
confidence: 99%
“…They found that accurate forecasting was needed to maximize revenue, and strategies aimed at both direct and indirect channels should be aligned to maximize value and cost-effectiveness [33]. For crisis management during COVID-19, Ivanov pointed out that automation technologies should be provided to tourism-related companies to mitigate the negative impacts of biosecurity threats on their economic performance [34]. In summary, crisis management plays an important role in revenue management from the evidence of existing studies.…”
Section: Revenue Management In the Hospitality Industry Associated Wimentioning
confidence: 99%